Researching Attitudes Related to Municipal Waste Management in Makarska (Vallis Aurea, 2015)
The research conducted aimed to prove that the ecological awareness of participants in the procedure of waste management in Makarska is not at a satisfactory level, though the cognitive and emotional component of the respondents’ attitudes is at a higher level than that of the behavioural component. However, the level of ecological awareness of all participants in waste management procedure in Makarska can be significantly improved by implementing strategies of attitude change. The research was conducted among three groups of respondents which included: tourists, the local population and catering facilities as the main users of waste disposal. The attitudes have been defined pursuant to a Likert’s scale consisting of 5 levels. The results obtained indicate that ecological awareness is low, but that the strategies of attitude change starting in childhood and in educational institutions can significantly increase the level of ecological awareness, and thus improve the behavioural components of attitudes in relation to cognitive and emotional components.